PRE-UNIVERSITY ENGINEERING TRAINING IN INTERNATIONAL MULTI-PARTNER EDUCATIONAL ENVIRONMENT - M. V. ZHURAVLEVA; L. V. OVSIENKO; N. Yu. BASHKIRTSEVA; L. R. IBRASHEVA; O. P. EMELYANOVA (Moscow Polytechnic University, 2018)
Modern world integration processes lead to an increase in demand for engineers with international level competences. This requires the improvement of continuous training. Pre-university engineering training is considered as a stage of applicants' orientation to engineering education and their adaptation to the complex educational process at university. This can be achieved by improving the content of education and including the technological, applied research and special linguistic components. The main directions of the content of the pre-university training are variable and have to be determined according to the tendencies of high-tech industries' integration into the international technological space. An important factor is the implementation of training in an international multi-partner scientific and educational environment, which involves the international production companies, international profile network associations and the international academic community in the educational process. This allows implementing effective forms of training, including the work in real research teams, networked educational programs, the use of virtual platforms and simulators. The Tatarstan Republic has innovative practical experience of pre-university engineering education of schoolchildren oriented to the needs of the regional oil and gas chemical complex. In this regard, Kazan National Research Technological University (KNRTU) implements pre-university training on the basis of the lyceum with advanced curriculum in Chemistry. Such training is organ-ized with the participation of regional partners of the Danish Corporation "Haldor Topsoe" and the European Chemistry Thematic Network Association (ECTNA). Pre-university engineering training develops shoolchildren's motivation for engineering education, has a professionally specified character of training and also comprises the changes in the content of the engineers' future professional activity.